Pengaruh Motivasi Intrinsik Dan Peraturan Pesantren Terhadap Kepuasan Santri Pondok Pesantren Manahijussadat Lebak, Banten - Saragih, Muhamad Nasrun; Sastradiharja, EE Junaedi; Zuhri, Saifuddin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
This study aims to test and determine whether empirically through valid data, intrinsic motivation and pesantren regulations have an effect on the satisfaction of students both partially and simultaneously. The method used by researchers is a survey method with a correlational approach to the santri of Manahijusadat Islamic Boarding School in Lebak, Banten. This type of research is quantitative, therefore the data analysis technique used is statistical analysis techniques, namely descriptive statistical techniques and inferential statistics. As for the means of collecting data through a questionnaire to 100 respondents from class III MTs Manahijussadat Islamic Boarding School, interviews and documentation. The results of the research hypothesis test showed that there was a positive and significant influence of intrinsic motivation on student satisfaction with a percentage of 17.8%. Second, there is a positive and significant effect of Islamic boarding school regulations on the satisfaction of students as indicated by the percentage of influence of 25.5%. Third, there is a joint positive and significant effect of intrinsic motivation and pesantren regulations on student satisfaction by 32.6%